Benzene-cored AIEgens for deep-blue OLEDs: high performance without hole-transporting layers, and unexpected excellent host for orange emission as a side-effect. Issue 7 (30th March 2016) - Zhan, Xuejun; Wu, Zhongbin; Lin, Yuxuan; Xie, Yujun; Peng, Qian; Li, Qianqian; Ma, Dongge; Li, Zhen
Abstract : For the first time, AIEgens with good hole-transporting ability served as emitting layer or host with high performance. Abstract : Great efforts have been devoted to explore efficient fluorescent materials, especially deep-blue luminogens, for organic light emitting diodes (OLEDs). In this paper, according to the design idea of creating luminogens with the characteristic of aggregation induced emission (AIE), four new benzene-cored luminogens with very simple structure have been intelligently designed, in which, without an additional hole-transporting layer (such as NPB), 3TPA-CN exhibited deep-blue emission and high performance in a simple nondoped LED device with a current efficiency (CE) of 5.21 cd A −1, external quantum efficiency (EQE) of 3.89%, and CIE coordinates of (0.15, 0.14). Excitingly, as a wonderful side-effect, 3TPA-CN can serve as an excellent host for orange emissive phosphorescent OLEDs (PhOLEDs), with a maximum current and power efficiency of 57.4 cd A −1 and 52.0 lm W −1, respectively, and a corresponding maximum EQE of 18.2%, higher than that of CBP (15.7%), one popular host for orange PhOLEDs, under the same conditions, thus broadening the utilization of AIEgens as host in PhOLEDs.